(untitled) (DAPesquisa, 2025)
To perceive, represent and inhabit the landscape of Córrego do Bação, in Itabirito, Minas Gerais, Brazil: this was the invitation made by the project entitled próxima paisagem: escola de arte provisória (“next landscape: provisional art school”). The project consists of an artistic residency, where each edition brings together a group of five participants[1]. Within the context of the second edition of the residency, I was part of “next landscape” Group No. 2[2] and, like all other residents, I elaborated poetic responses to the proposition of immersing ourselves in the landscape of Córrego do Bação. In this paper, I describe four works created based on the experiences and experiments that took place with the landscape. Throughout these repeated visits to the region, intimacy, light and the act of inhabiting a space proved to be the main elements connecting the propositions that I developed. Keywords: landscape, artistic residency, inhabiting, Córrego do Bação, photography [1] The research project “next landscape: provisional art school” is proposed by artist, professor and researcher FT, who also forms part of the groups. [2] The project was conducted in connection with the Institutional Scientific Initiation Scholarship Program of the Minas Gerais State University (UEMG), Brazil, under CNPq tender 04/2019. I took part in the project as a scholarship student. “next landscape” Group No. 2 is still in activity, elaborating and implementing actions to publish the resulting works. It is expected to be dissolved in December 2021.